"Two schools within a school": Elitism, divisiveness, and intra-racial gentrification in a dual language strand. Issue 2 (3rd April 2021) - Freire, Juan A.; Alemán, Enrique
ABSTRACT: With most elementary dual language bilingual education (DLBE) programs being implemented as strands within schools, tensions related to inequities, unequal distribution of resources, and academic quality and demographic differences often arise. Based on a longitudinal ethnographic study and two interview phases with DLBE and mainstream teachers, this study analyzes teachers' perceptions and discourses regarding tensions related to the Spanish-English two-way bilingual education program at their urban elementary school. Findings from a thematic analysis approach pointed to teachers' discourses of elitism and divisiveness in relation to the DLBE strand based on racial tensions and school inequities, including what we call intra-racial DLBE gentrification. These findings are based on how educators experienced tensions regarding this bilingual program related to (a) the composition of the student body in terms of perceived quality and quantity, (b) cognitive and academic benefits, (c) resources provided by a university partnership, and (d) parental involvement. Implications for administrators and teacher preparation programs toward equity and school integration with DLBE strands are discussed.